2019
DOI: 10.34172/ajdr.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Iatrogenic Errors and the Quality of Root Canal Treatment of Mandibular Premolars in Ardabil Population Using the Cone Beam Computed Tomography in 2018

Abstract: BackgroundThe bacterial elimination of the root canal system holds the key to successful endodontic treatment (1) and implementing a thorough and meticulous technique is considered as the primary determinant to achieve this aim and thus to prevent the future encroachment of bacteria. Therefore, the success rate can be as high as 94% when these measures are taken into account

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Tese rates were 23.3% and 15.3%, respectively, in a study by Mozayeni et al [38] in a dental school in Tehran, Iran, 21% and 9%, respectively, in a study by Lynch and Burke [39], and 37.3% and 7.8%, respectively, in a study by Ilgüy et al [5] on dental students in Turkey. Nouroloyouni et al [22] also reported that underflling was the most common error in the second and frst mandibular premolars (9.5% compared with 9.2%), respectively. In addition, overflling was the second most common error in this study (6.3%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tese rates were 23.3% and 15.3%, respectively, in a study by Mozayeni et al [38] in a dental school in Tehran, Iran, 21% and 9%, respectively, in a study by Lynch and Burke [39], and 37.3% and 7.8%, respectively, in a study by Ilgüy et al [5] on dental students in Turkey. Nouroloyouni et al [22] also reported that underflling was the most common error in the second and frst mandibular premolars (9.5% compared with 9.2%), respectively. In addition, overflling was the second most common error in this study (6.3%).…”
Section: Discussionmentioning
confidence: 95%
“…Te CBCT is also a highly advantageous educational instrument. With the aid of CBCT, the quality of endodontic treatments and iatrogenic errors can be determined utilizing existing archives that reveal the weak points of clinicians, allowing for target-based learning to reduce these weaknesses [22].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of RCT and incidence of procedural errors can vary between general dentists and endodontists and also among different regions, as documented in several studies [4][5][6][7][8]. Procedural errors can include missed canals (detecting an unfilled root canal by changing the radiographic angle), over-or underfilled canals (overfilling beyond the tooth apex, underfilling by >2 mm short of the root apex), and root perforations (communication between the root canal system and periodontium), as well as instrument separation (presence of a broken piece of instrument in the root canal space or in the periapical area) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Procedural errors can include missed canals (detecting an unfilled root canal by changing the radiographic angle), over- or underfilled canals (overfilling beyond the tooth apex, underfilling by >2 mm short of the root apex), and root perforations (communication between the root canal system and periodontium), as well as instrument separation (presence of a broken piece of instrument in the root canal space or in the periapical area) [ 9 ]. Previous studies have reported that the most frequent procedural errors were ledges [ 10 ], underfilled canals [ 6 , 11 ], and inadequate radiopacity of the root filling [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation